Integrated Vehicle Routing and Cold Chain Optimization with Seasonal Variability Simulation for Fresh Fruit Distribution Networks - Baladraf, Thabed Tholib (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Cold supply chains are critical for maintaining quality and quantity of fresh fruit commodities under seasonal variability, energy, and cost constraints. This study aims to (1) identify the most efficient vehicle routing algorithm to minimize fleet size and distance; (2) evaluate delivery performance through simulation under four scenarios (basic, adaptive, collaborative, technological); and (3) determine effective logistics risk management strategies. A spatial-variation heuristic was applied for routing, dynamic simulation for scenario analysis, and qualitative methods for risk strategies. Results show the sweep heuristic algorithm as most efficient, reducing shipping costs and distances by 33.02%, maximum travel time by 41.7%, and energy use by 29.49%. Scenario analysis identifies the technological scenario integrating AI, blockchain, and IoT as most optimal, ensuring cost-efficiency, truck utilization, fulfillment rate, minimal product loss, and flexibility. Recommended risk strategies include predictive systems, hybrid transportation, joint capacity investments, and adaptive refrigeration to strengthen cold chain resilience.